Perancangan dan analisis kekuatan statis pada fixed-portable hydraulic scissor car lift platform dengan kapasitas 2 ton - Igor Vinicius De Souza Lima; J Victor Tuapetel; Achmad Zaki Rahman (University of Muhammadiyah Jakarta, 2022)
The large number of vehicles (cars) currently available causes an increase in demand for vehicle services and maintenance. Required availability of equipment that results in effectiveness and efficiency in its maintenance. The scissor lift model was chosen because it is portable and does not require much space for use in workshops. The design of a lifting device that uses a scissor lifting type hydraulic system that can be used fixed-portable for MPV type vehicles or vehicles weighing under 2 tons was carried out. The designed platform is then calculated and analyzed for its structural strength using FUSION 360 and FTOOL software. The calculation results show that the total stress is less than the permissible stress , then the material meets the strength requirements () and is declared safe. From the FEA Stress Von Mises simulation results, the total stress on the structure is smaller than the material stress. Due to the calculation using = 1.5 and the safety factor from the simulation results is greater than the safety factor used in the design, the design meets the strength requirements and is declared safe.